From unemployment to self-employment: The role of entrepreneurship training - Marios Michaelides; Scott Davis (IZA Journal of Labor Policy, 2020)
We present experimental evidence on the effects of entrepreneurship training for unemployed workers in the U.S. at two different stages in the business cycle. In the context of a strong economy, training helped training participants - particularly those with prior self-employment experience - to start a business and become self-employed, while it may have persuaded others to pursue salary employment instead. During the Great Recession, training helped training participants become self-employed, particularly those with no prior self-employment experience. Regardless of economic conditions, positive impacts on self-employment were partly or largely offset by reductions in regular employment. These findings indicate that entrepreneurship training may help unemployed workers to become self-employed at different stages of the business cycle, but there is weak evidence that it can be an effective policy for combating unemployment, particularly during recessions.
Keywords: J6; H4; 330; Great Recession; self-employment; entrepreneurship; start-up; small business; entrepreneurship training; unemployment; policy evaluation; reemployment